Sete erros - Lovato, Ana Luiza Tonietto (2021)
The present dissertation consists of the novel Seven mistakes and the essay Notes on creation. The novel deals with the pregnancy of Maria Antonia, a 32-year-old doctor, and the premature birth of her daughter. While she remains in an unconscious state, due to eclampsia, a witness narrator alternates with an omniscient narrator, weaving a plot that unites the story of four generations of women in the family, having motherhood and the violence to which women are subjected as a background. The essay section reflects on the creative process of the work, from literary creation theorists, such as Luiz Antonio de Assis Brasil, in Escrever ficção - um manual de criação literária; Rosa Montero, in A louca da casa; and Cecília Almeida Salles, in Gesto inacabado - processo de criação artística.